Efficacy and safety of cannabinoid oromucosal spray for multiple sclerosis spasticity. Issue 9 (9th May 2016) - Patti, F; Messina, S; Solaro, C; Amato, M P; Bergamaschi, R; Bonavita, S; Bruno Bossio, R; Brescia Morra, V; Costantino, G F; Cavalla, P; Centonze, D; Comi, G; et al.
Abstract : Background: The approval of 9-δ-tetrahydocannabinol and cannabidiol (THC:CBD) oromucosal spray (Sativex) for the management of treatment-resistant multiple sclerosis (MS) spasticity opened a new opportunity for many patients. The aim of our study was to describe Sativex effectiveness and adverse events profile in a large population of Italian patients with MS in the daily practice setting. Methods: We collected data of all patients starting Sativex between January 2014 and February 2015 from the mandatory Italian medicines agency (AIFA) e-registry. Spasticity assessment by the 0–10 numerical rating scale (NRS) scale is available at baseline, after 1 month of treatment (trial period), and at 3 and 6 months. Results: A total of 1615 patients were recruited from 30 MS centres across Italy. After one treatment month (trial period), we found 70.5% of patients reaching a ≥20% improvement (initial response, IR) and 28.2% who had already reached a ≥30% improvement (clinically relevant response, CRR), with a mean NRS score reduction of 22.6% (from 7.5 to 5.8). After a multivariate analysis, we found an increased probability to reach IR at the first month among patients with primary and secondary progressive MS, (n=1169, OR 1.4 95% CI 1.04 to 1.9, p=0.025) and among patients with >8 NRS score at baseline (OR 1.8 95% CI 1.3–2.4 p<0.001). During the 6 months observation period, 631(39.5%) patients discontinued treatment. The main reasons for discontinuation were lack of effectiveness (n=375, 26.2%) and/or adverse events (n=268, 18.7%). Conclusions: Sativex can be a useful and safe option for patients with MS with moderate to severe spasticity resistant to common antispastic drugs.